2019
DOI: 10.35333/jrp.2019.74
|View full text |Cite
|
Sign up to set email alerts
|

Chemical analysis and in vitro antioxidant and anticholinesterase activities of essential oils and extracts from different parts of Erica manipuliflora

Abstract: This study reports the chemical composition of essential oils and in vitro antioxidant and anticholinesterase activities of essential oils, hexane, ethyl acetate, methanol, and butanol extracts of aerial, flower and leaves parts of Erica manipuliflora. GC and GC/MS analyses were used for identification of essential oils. Totals of 47 compounds were detected in the essential oils of aerial, flower and leaves parts accounting for 99.99%, 99.88% and 99.97%, respectively. The major components of the aerial, flower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 25 publications
0
8
3
Order By: Relevance
“…The other main distinct components in EO of E. manipuliflora collected in full flowering period were Transcaryophellene, Verbenol, β-bisabolene, which represented 7.61, 2.19, 2.15%, respectively, and were absent in the EO of E. manipuliflora collected before flowering period. The percent of verbenol was higher than that recorded by Kuş et al 36 , who found that the verbenol represents 1.17% in the EO extracted from E. manipuliflora flower part.…”
Section: Gas Chromatography-mass Spectrometry Analysiscontrasting
confidence: 72%
See 3 more Smart Citations
“…The other main distinct components in EO of E. manipuliflora collected in full flowering period were Transcaryophellene, Verbenol, β-bisabolene, which represented 7.61, 2.19, 2.15%, respectively, and were absent in the EO of E. manipuliflora collected before flowering period. The percent of verbenol was higher than that recorded by Kuş et al 36 , who found that the verbenol represents 1.17% in the EO extracted from E. manipuliflora flower part.…”
Section: Gas Chromatography-mass Spectrometry Analysiscontrasting
confidence: 72%
“…The major compound was Germacrene-D, which represented 35.02 and 16.90% in the EOs extracted from aerial parts of this plant in the two growth periods (before flowering and full flowering, respectively). These values were higher than that recorded by Kuş et al 36 (14.76 and 15.55%, in aerial parts and flower part, respectively); followed by tau-cadinol (26.36 and 11.89% respectively in the two growth periods mentioned above). These values were higher than that recorded by Kuş et al 36 which were 7.53 and 4.11% in the aerial parts and flower part, respectively.…”
Section: Gas Chromatography-mass Spectrometry Analysiscontrasting
confidence: 70%
See 2 more Smart Citations
“…Medicinal and aromatic plants have been used for a variety of purposes worldwide since ancient times [1,2,3]. Nowadays, essential oils are primarily used in cosmetic, pharmaceutical and food industries [4,5,6]. For this reason, plants that can produce essential oils have a strong position as economic products worldwide so the market of essential oils is growing in time [7].…”
Section: Introductionmentioning
confidence: 99%